Effects of Sulphur Deficiency on Accumulation of K+, Na+, NO3-, PO43- and transport of K+, Na+ in mungbean (Vigna radiata L. var. BARI MUNG-6) - Saha, Shukanta; Samad, Rifat; Rashid, Parveen; Karmoker, JL (Dhaka University Journal of Biological Sciences, 2016)
Sulphur deficiency caused a decrease in accumulation of Na+ but increased the accumulation of K+ in the root, stem and leaf of mungbean seedlings grown in solution culture under light bank. It also decreased K+ and Na+ accumulation in the root, stem and leaf of mungbean plants grown in sand culture under natural environmental conditions. However, sulphur deficiency increased the accumulation of NO3- in the root and stem but decreased that in leaf of mungbean seedlings grown in solution culture. It decreased accumulation of PO43- in the root, stem and leaf except an initial increase in the leaf. It increased net influx, long distance transport and transport index of K+ but decreased those of Na+ in mungbean seedlings. This result indicates that K+ is more mobile in plants than Na+. Dhaka Univ. J. Biol. Sci. 25(2): 123-130, 2016 (July)